2013
DOI: 10.1242/jcs.130039
|View full text |Cite
|
Sign up to set email alerts
|

A cell-based fascin bioassay identifies compounds with potential anti-metastasis or cognition-enhancing functions

Abstract: SUMMARYThe actin-bundling protein fascin is a key mediator of tumor invasion and metastasis and its activity drives filopodia formation, cell-shape changes and cell migration. Small-molecule inhibitors of fascin block tumor metastasis in animal models. Conversely, fascin deficiency might underlie the pathogenesis of some developmental brain disorders. To identify fascin-pathway modulators we devised a cell-based assay for fascin function and used it in a bidirectional drug screen. The screen utilized cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 110 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…However, some widely used TCAs, such as imipramine, desipramine, and amitriptyline, have emerged as possible promising repurposing drugs in colorectal cancer [116]. Following this line, in 2020, Alburquerque-Gonzalez et al showed that imipramine attenuated cell migration and invasion of colorectal cancer cells by inhibition of fascin [71], a key protein in actin bundling that plays a causative role in tumor invasion and is overexpressed in different cancer types with poor prognosis [117]. This was the first study that demonstrated an antitumoral role of imipramine as a fascin inhibitor [118].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…However, some widely used TCAs, such as imipramine, desipramine, and amitriptyline, have emerged as possible promising repurposing drugs in colorectal cancer [116]. Following this line, in 2020, Alburquerque-Gonzalez et al showed that imipramine attenuated cell migration and invasion of colorectal cancer cells by inhibition of fascin [71], a key protein in actin bundling that plays a causative role in tumor invasion and is overexpressed in different cancer types with poor prognosis [117]. This was the first study that demonstrated an antitumoral role of imipramine as a fascin inhibitor [118].…”
Section: Colorectal Cancermentioning
confidence: 99%